PERSEPSI MASYARAKAT MENGENAI TRADISI MANDI SAFAR DITINJAU DARI NILAI PANCASILA DI DESA SUNGAI BULUH KECAMATAN SINGKEP BARAT KABUPATEN LINGGA KEPULAUAN RIAU - Urai Azelia Santika Nandra; Zahirman '; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is in the background by one tradition in Malay society, which tradition is commonly called Safar Bath. The existence of safar bath tradition is currently being carried out in the Malay community of Sungai Buluh Village. The formulation of the problem in this research is how is the public perception of safar bath tradition in terms of the value of Pancasila in the village of Sungai Buluh regency lingga Riau Islands ?. The purpose of this research is to know public perception about safar bath tradition in terms of value of pancasila in rivers river village regency lingga riau archipelago. The population of this study is the entire community in Sungai Buluh Village which is 1745 people and 540 kk. According to opinion (Sugiyono, 2013: 124) To determine the size of the sample then the author uses purposive sampling. Purposive sampling is a technique of taking or determining the sample with certain considerations. Based on the opinion Sugiyono that researchers allowed to determine the desired sample with certain considerations and in harmony with the purposive sampling of 30 people. Data collected through observation, questionnaires, interviews, and library techniques. In the data analysis using qualitative descriptive analysis.Based on the results of this study it can be concluded that the percentage of respondents' responses recapitulation answer about the perception of the community about the safar bath tradition in terms of the value of Pancasila in the village of Sungai Buluh sub-district of West Singkep regency lingga Riau Islands, which answered "Yes" 63,6 who answered "No" 36,4% Hypothesis which states that there are values of Pancasila in the tradition of Safar Baths in Sungai Buluh Village, Singkep Barat District, Lingga Regency, Riau Islands.Keywords: Pancasila Values, Safar Bath Tradition